Ação de despejo nas locações prediais urbanas - Rodrigues, Michael Antonio Garcia (2011)
The law number 8,245/91, also known as Rental Law or Tenant Law regulates the rental of urban buildings. Through this work we show in a didactic and elucidative way, the rules, procedures and legal disposition applicable to the real estate rental institution in Brazil. The studies pass through a brief rental historical analysis and about the appearance of the specific legislation in several countries worldwide. The importance to identify and classify correctly all kinds of rental, demonstrates as a useful tool to make good use of rights or even allow to return the building according to a specific legal forecast that regulates the oral rentals or those ones where do not exist any written rental agreement or contract. The knowledge about the landlord and tenant’s rights and duties has great importance when renting a building. The several kinds of rental guarantee under the law number 8,245/91, search to develop the rental and to reduce the risks of defaulting. This work emphasizes on hypothesis that lead to lawsuits of eviction such as: a) lack of payment; b) return to own use; c) return for repairs, demolition and licensed construction; d) uninterrupted validity of the residential rental for more than five years; e) the expiration of the commercial rental contract, being impossible the judicial renovation. Although it was intended to show the advantages of knowing the conditions in which the order of eviction may be granted preliminarily, reducing sensitively the deadline to disoccupy the building. Finally this work also talks about the sentence of eviction, its temporary execution and eventual appeal, ending the studies with the civil and criminal penalties that can be applied to the landlord for transgression of the rental law